2013
DOI: 10.1523/jneurosci.2345-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Maturation of the Executive System during Adolescence

Abstract: Adolescence is characterized by rapid development of executive function. Working memory (WM) is a key element of executive function, but it is not known what brain changes during adolescence allow improved WM performance. Using a fractal n-back fMRI paradigm, we investigated brain responses to WM load in 951 human youths aged 8 -22 years. Compared with more limited associations with age, WM performance was robustly associated with both executive network activation and deactivation of the default mode network. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
227
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(254 citation statements)
references
References 87 publications
26
227
1
Order By: Relevance
“…Thus it is critical that computational models incorporate developmental changes in synaptic and circuit function in diseaserelated models. For instance, the human neural representation of working memory assessed with fMRI changes during adolescence (Satterthwaite et al 2013). Similarly, synaptic mechanisms evolve during adolescence.…”
Section: Looking Forward: Building a New Cross-disciplinary Fieldmentioning
confidence: 99%
“…Thus it is critical that computational models incorporate developmental changes in synaptic and circuit function in diseaserelated models. For instance, the human neural representation of working memory assessed with fMRI changes during adolescence (Satterthwaite et al 2013). Similarly, synaptic mechanisms evolve during adolescence.…”
Section: Looking Forward: Building a New Cross-disciplinary Fieldmentioning
confidence: 99%
“…Despite the fact that the 5-to-7 shift has been an important topic in developmental psychology research, the emerging field of developmental cognitive neuroscience has thus far been silent about it. Although functional MRI (fMRI) studies have demonstrated a close link between development of cognitive control during middle childhood and adolescence and the maturation of frontoparietal circuitry (e.g., Luna et al, 2001;Satterthwaite et al, 2013), fMRI studies focusing specifically on the age range of 5 to 7 have been sparse (but see Sheridan, Kharitonova, Martin, Chatterjee, & Gabrieli, 2014). Electroencephalography (EEG) studies that have looked at cognitive control during this age range have revealed an age-related increase in the error positivity (Grammer, Carrasco, Gehring, & Morrison, 2014) and a positive association between the error positivity and early academic achievement (Kim et al, 2016).…”
mentioning
confidence: 99%
“…Anatomical changes in the prefrontal cortex continue during adolescence, involving gray and white matter volumes and myelination of axon fibers within the prefrontal cortex and between the prefrontal cortex and other areas (8-15). Changes in prefrontal activation, including increases (12,(16)(17)(18)(19)(20) and decreases (21, 22), have been documented in imaging studies for tasks that require inhibition of prepotent behavioral responses and filtering of distractors.Much less is known about how the physiological properties of prefrontal neurons develop after puberty. Similar to the human pattern of development, the monkey prefrontal cortex undergoes anatomical maturation in adolescence and early adulthood (23,24).…”
mentioning
confidence: 99%
“…Anatomical changes in the prefrontal cortex continue during adolescence, involving gray and white matter volumes and myelination of axon fibers within the prefrontal cortex and between the prefrontal cortex and other areas (8)(9)(10)(11)(12)(13)(14)(15). Changes in prefrontal activation, including increases (12,(16)(17)(18)(19)(20) and decreases (21,22), have been documented in imaging studies for tasks that require inhibition of prepotent behavioral responses and filtering of distractors.…”
mentioning
confidence: 99%